Blimp-1 signaling pathways in T lymphocytes is essential to control the Trypanosoma cruzi infection-induced inflammation - Benevides, Luciana; Sacramento, Lais A.; Pioto, Franciele; Barretto, Gabriel Dessotti; Carregaro, Vanessa; Silva, João S. (Frontiers in Immunology, 2023)
In many infectious diseases, the pathogen-induced inflammatory response could result in protective immunity that should be regulated to prevent tissue damage and death. In fact, in Trypanosoma cruzi infection, the innate immune and the inflammatory response should be perfectly controlled to avoid significant lesions and death. Here, we investigate the role of Blimp-1expression in T cells in resistance to T. cruzi infection.Therefore, using mice with Blimp-1 deficiency in T cells (CKO) we determined its role in the controlling parasites growth and lesions during the acute phase of infection.Infection of mice with Blimp-1 ablation in T cells resulted failure the cytotoxic CD8 + T cells and in marked Th1-mediated inflammation, high IFN-g and TNF production, and activation of inflammatory monocyte. Interestingly, despite high nitric-oxide synthase activation (NOS), parasitemia and mortality in CKO mice were increased compared with infected WT mice. Furthermore, infected-CKO mice exhibited hepatic lesions characteristic of steatosis, with significant AST and ALT activity.Mechanistically, Blimp-1 signaling in T cells induces cytotoxic CD8 + T cell activation and restricts parasite replication. In contrast, Blimp-1 represses the Th1 response, leading to a decreased monocyte activation, less NOS activation, and, consequently preventing hepatic damage and dysfunction. These data demonstrate that T. cruziinduced disease is multifactorial and that the increased IFN-g, NO production, and dysfunction of CD8 + T cells contribute to host death. These findings have important implications for the design of potential vaccines against Chagas disease.